Adsorption of a cationic dye (Methylene bleu) by Typha Latifolia: Equilibrium, kinetic, thermodynamic and DFT calculations - Amri, Abdelhay El; Bensalah, Jaouad; Idrissi, Abdennacer; Lamya, Kadiri; Ouass, Abdelkarim; Bouzakraoui, Said; Zarrouk, Abdelkader; Rifi, El Housseine; Lebkiri, Ahmed (Chemical Data Collections, 2022)
In this work, the adsorption performance of methylene blue (MB) on rough R and Typha Latifolia RS was studied. On one hand, the effect of various parameters on the adsorption efficiency were studied knowing that the mass of the material, the adsorption time, the initial concentration and the pH of solution. All these different parameters influence the absorption capacity. The maximum amount of adsorption of the different materials studied are estimated at 21.01 mg g−1 and 54.73 mg g−1 at pH = 5. Under all optimal conditions, the relevant MB removal rates at R and RS were 69.62% and 91.09%, respectively. On the other hand, the mathematical modeling studied has shown that the S-type adsorption process and that the pseudo second order and Langmuir are the most suitable models to describe the adsorption of the cationic dye via R and RS. In fact, the study of Langmuir and Freundlich parameters has indicated that the removal of MB by R and RS is favorable. Moreover, Theoretical calculations were carried out using simulations of the (DFT) explored the interaction between the most reactive sites concerning the major biosorbent constituent Typha Latifolia which is the cellulosic polymer and the cationic dye MB. The comparative study of all experimental and theoretical results has confirmed the biosorption potential of the studied biosorbent for the removal of dyes.